Birth Outcomes, Health, and Health Care Needs of Childbearing Women following Wildfire Disasters: An Integrative, State-of-the-Science Review - Evans, Jo; Bansal, Amita; Schoenaker, Danielle A.J.M.; Cherbuin, Nicolas; Peek, Michael J.; Davis, Deborah L. (Environmental health perspectives, 2022)
The frequency and severity of extreme weather events such as wildfires are expected to increase due to climate change. Childbearing women, that is, women who are pregnant, soon to be pregnant, or have recently given birth, may be particularly vulnerable to the effect of wildfire exposure. This review sought to systematically assess what is known about birth outcomes, health, and health care needs of childbearing women during and after exposure to wildfires. An integrative review methodology was utilized to enable article selection, data extraction, and synthesis across qualitative and quantitative studies. Comprehensive searches of SCOPUS (including MEDLINE and Embase), CINAHL, PubMed, and Google Scholar identified studies for inclusion with no date restriction. Included studies were independently appraised by two reviewers using the Crowe Critical Appraisal Tool. The findings are summarized and illustrated in tables. Database searches identified 480 records. Following title, abstract, and full text screening, sixteen studies published between 2012 and 2022 were identified for this review. Eleven studies considered an association between exposure to wildfire and impacts on birth weight and length of gestation. One study reported increased rates of maternal gestational diabetes mellitus and gestational hypertension following exposure; whereas one study reported differences in the secondary sex ratio. Two studies reported higher incidence of birth defects following exposure to wildfire smoke. Three studies reported increased mental health morbidity, and one study associated a reduction in breastfeeding among women who evacuated from a wildfire disaster. Evidence indicates that wildfire exposure may be associated with changes to birth outcomes and increased morbidity for childbearing women and their babies. These effects may be profound and have long-term and wide-ranging public health implications. This research can inform the development of effective clinical and public health strategies to address the needs of childbearing women exposed to wildfire disaster. https://doi.org/10.1289/EHP10544.